Enforcement of the Ottoman Vilayet Law in the Districts of the Sanjak of Zvornik - Amir Krpić (Društvene i Humanističke Studije, 2022)
This paper is about the implementation of the 1865/67 Ottoman Vilayet Law in the districts of the Sanjak of Zvornik. At first, there were listed those articles of the Law regarding the level of districts (kazas). After that, using the Ottoman annual reports for the Vilayet of Bosnia, there were listed the local governing institutions, services, and officials’ names for each district in the first four years after the announcement of the Vilayet Law. Based on these data, one can conclude that the Law has certainly been implemented in the districts belonging to the Sanjak of Zvornik.